Desenvolvendo o resultado do cubo da diferença (X - 2)³ obtemos??
ME AJUDEM PORFAVOR!! !
Soluções para a tarefa
Respondido por
0
Resposta:
x³ - 6x² + 12x - 8
Explicação passo-a-passo:
(a - b)³⇒ a³ - 3a²b + 3ab² - b³
então
(x - 2)³ ⇒ x³ - 3x².2 + 3x.2² - 2³
(x - 2)³ ⇒ x³ - 6x² + 12x - 8
Perguntas interessantes
História,
8 meses atrás
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Ed. Moral,
10 meses atrás
Matemática,
10 meses atrás
Administração,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás